The economic efficiency of the circular economy in the construction sector in Colombia - Colmenares – Rueda , Harold Andrés; Paredes – Bayona , Nahúm Emiro; Chicacausa – Navarrete, Cristian Felipe; González – Bula , Steveen Alexander (Universidad Francisco de Paula Santander, 2021)
The construction sector in its favorable contribution to modernization and the country's economy, makes use of highly polluting raw materials, which when discarded at the end of their cycle generate a high impact on the environment, for this reason the purpose of this research focused on the recovery and reinsertion of said waste into the economy. For this reason, the economic efficiency presented by the circular economy models compared to the construction sector in Colombia was analyzed. This project was carried out with a type of research with a qualitative approach, with a descriptive scope. The type of research in which the methodological design was framed was an action research, as a technique a documentary review was implemented, where thestatistical and sustainability reports of the construction sector were part of the information used. As a result of the research, it was initially possible to identify the circular economy models applied in the construction sector. Likewise, the economic-environmental impact of these could be analyzed. Finally, the feasibility of using circular economy models in the construction sector was determined. Concluding that the circular economy is a strategy that allows addressing the new challenges facing the construction sector in Colombia.